PERAN BIMBINGAN. PRA. NIKAH. TERHADAP CALON. PENGANTIN. YANG MENIKAH DINI DALAM. MEMBENTUK KELUARGA. SAKINAH. (STUDI. KASUS. DI KUA. KECAMATAN. JUNREJO KOTA BATU) - Nadea Octamia Putri; Ahmad Subekti; Faridatus Sa’adah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
Early marriage is a marriage carried out by a man and a woman who are under the age of 19 years or in accordance with the marriage law No. 16 of 2019 which explains that the age of a person can marry for men and women at least 19 years old. In early marriage, various problems often occur, the cause of which is because they still prioritize high egotism in dealing with problems, it can even lead to divorce. So, the role of premarital guidance is very much needed to foster early marriage prospective brides. In this study, researchers used a descriptive research method, namely a case study in KUA, Junrejo sub-district, Batu City. The data was obtained by using interview, observation and documentation methods. The results of this study are, the guidance policy has a good impact on prospective brides who marry early, in order to provide knowledge about how to build a samawa household, and provide solutions in solving good problems. Because people who marry underage still often have unstable thoughts and uncontrolled ego. Key Words: Role, Pre-Marriage Guidance, Bride and Groom, Early Marriage, Sakinah Family